Automobile display and payment plan calculator system / Mohamed Fazil Abdul Salam - Abdul Salam, Mohamed Fazil (2004)
The Automobile Display and Payment Plan Calculator System is a system which helps both the customer and the sales personnel during the process of selling/buying a vehicle. The system incorporates a display system that is able to present multiple views of the vehicles available for sale to the customer, including a 360° external view of the vehicle. The system is also capable of formulating a Payment Plan for the customer so that they can scrutinise their choices better. In cases where the customers are not able to a purchase the vehicle of their choice, an agent within the system is at hand to help the customer by providing alternative choices to the customer. This system is the product of this project. This thesis will detail all the work that goes into planning, constructing and implementing the system.